동시대 조각가의 사용 재료 변화 추이 연구 국내 주요 - 레지던시 입주 조각가를 중심으로 - 양태근; Tea Geun Yang; 차주용; Zoo Yong Cha (기초조형학연구, 2016)
본 논문의 연구목적은 한국 주요 레지던시(Residency) 입주 작가 중 조소 전공자들을 통해서 본 동시대 한국 조각가의 시대별 재료 사용 변화의 특성을 분석하는 것에 있다. 한국을 대표하는 레지던시 5곳(국립현대미술관 창동·고양 레지던시, 서울시립미술관 난지미술창작스튜디오, 서울시 창작공간 금천예술공장, 경기도미술관 경기창작센터, 인천시 인천아트플랫폼)에 입주해서 활발하게 작품 활동을 해온 동시대 예술가 중 조소를 전공한 조각가들의 지난 14년간(2002∼2015)의 활동을 추적해 동시대 조각가들의 재료사용현황과 재료사용의 변화의 흐름을 파악하고 분석했다. 연구 결과, 전통적인 조소 재료인 석재, 금속재, 목재 등의 단일재료로 이루어진 작업을 하는 조각가는 점점 줄어드는 추세를 보였으며, 여러 가지 매체를 사용하는 복합매체 표현 방식의 특성을 보였다. 즉, 설치, 영상, 사진, 퍼포먼스 등의 다매체를 활용한 비조각적 작업을 하는 조각가가 늘어나며 전통적 의미에서의 조소 전공 조각가의 의미가 퇴색되는 경향이 뚜렷했다. 이와 동시에 예술가의 활동을 지원하는 레지던시의 출현과 작가지원 프로그램은 이들 레지던시 입주 작가 서로에게 긍정적인 영향을 주고받으며 다양한 표현 방식에 영향을 주었다. 이런 현상은 더 많은 레지던시의 확산에 이바지하며 수많은 예술가의 관계성을 통해 한국의 현대 미술이 나아갈 방향을 제시하고 있다. 위에서 열거한 바와 같이 공신력 있는 레지던시의 입주 작가들을 대상으로 설정, 국내 최초로 이곳에서 입주한 예술가들의 작업형태를 추적하고 재료사용 변화과정을 분석, 연구하는 것에 그 의의가 있다 하겠다. The purpose of the study is to analyze the characteristics of the change in materials by period used by contemporary Korean Sculptors among the artists who moved into the major Korean residencies. The current state and the change of materials used by contemporary sculptors were identified and analyzed by tracking the performances of sculptors for the last 14 years (2002~2015) who majored in sculpture among contemporary artists, actively working and living in the 5 residencies representing Korea (Changdong and Goyang residency in the National Museum of Contemporary Art, Nanji residency in Seoul Museum of Art, Geumcheon Art Factory in Seoul Art Space, Gyeonggi Creation Center in Gyeonggi Museum of Modern Art, and Incheon Art Platform in Incheon). According to the study results, the numbers of sculptors who are working with single materials using the traditional sculpting materials such as stone, metal, wood, etc. showed a gradual decrease while many showed the characteristics of complex media expression method using various media. In other words, as more sculptors work on non-sculptural arts with multi-media such as installation, video, photography, performances, etc., the significance of sculptors majored in sculpture in the traditional sense is diminished. At the same time, emergence of residency which supports the activity of artists and artist support programs affected various expression methods of residency artists by providing positive influence to each other. This will contribute to expansion of more residencies and suggest the future-oriented direction for Korean modern art through relations of numerous artists. As mentioned above, this study is targeted on artists who moved into the first reputable residencies in Korea and the key of the study is to track and analyze their works.